Peradilan Islam; Historisitas Konsep Alat Bukti dan Relevansinya dalam Penegakan Keadilan di Era Modern - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2021)
The justice has been known since time immemorial because it is driven by the necessities of life and human events itself. It is impossible for a government in this world, whatever its form, will stand without upholding justice because there is no way a society can avoid conflict. Islamic law cannot be separated from the reality of people's life. Therefore, in society, a regulatory system is needed which is no other than the provisions contained in Islamic law, then its need a judicial institution which in Islam is called al-Qad}a>, which is an institution that is tasked with regulating problems that arise in. With changes in culture from time to time or life situations have changed and the rules continue to evolve. So it is very important to study the history of Islamic justice during the time of the Prophet and thereafter as well as the concept of evidence to seek the essence of truth, so that human rights are not neglected. Therefore, the extent to which the evidence for the Islamic judiciary period is compatible with the judiciary in the modern era (positive law); relevance, similarities and differences. This concept is none other than confession (iqra> r), bayyinah, and rejection of oaths (nuku>l qasa> mah). Keyword: Justice of Islam, the concept of evidence, The Justice.